Interspecies Park Life: Participatory Experiments and Micro-Utopian Landscaping to Increase Urban Biodiverse Entanglement. Issue 4 (November 2022) - Knudsen, Britta Timm; Stage, Carsten; Zandersen, Marianne
This article analyses the design and outcomes of the research project Rewilding Lystrup, which involved a partnership with local authorities in Aarhus, Denmark, to merge two distinct processes: climate adaptation and the biodiversity transformation of a public park. Our key interest in the article is the potential offered by experimental participatory events to support the biodiverse transformation of public areas by creating micro-utopian entanglements of citizens and nonhuman organisms. The article will focus on three experimental participatory events enacted as part of the research project: (1) public dialogues and workshops, (2) the arrival on the scene of charismatic cows, and (3) pop-up events in the form of participatory playing. The article concludes that this kind of material citizenship is a powerful strategy for stimulating public engagement in building more biodiverse futures. The strategy thus materializes micro-utopian spaces where the importance of biodiversity can be rehearsed and sensed by local communities. In this way, a culturally transformative zone of dreaming while doing—or doing dreams—is enacted.